Some Fundamental Research Tools in Mathematical Sciences - Khadka, Shree Ram; Ghimire, Santosh; K.C, Durga Jang (Journal of Nepal Mathematical Society, 2023)
Research in mathematical sciences either builds up the insight or breaks the boundary of the literature of the pertaining mathematical research area. A mathematical research technique is an attentive, persistent and systematic approach based on the logical rules of inference and mathematical rules of inference to find something new. Mathematical modeling, construction of theorems with the proofs, design of algorithms, data with simulation could be considered as the fundamental tools in mathematical research. In this paper, we discuss some fundamental research tools which are useful to do research in mathematical sciences.